Digital and Manual Rotation of the Persistent Occiput Posterior Fetus. (3rd June 2020) - Elmore, Christina; McBroom, Kelly; Ellis, Jessica
Abstract: Persistent fetal occiput posterior (OP) position is a topic of interest with implications for intrapartum management. Although studies report a low incidence of persistent OP position, anecdotal evidence suggests an increase in prevalence given changes in maternal demographics. Clinicians are often familiar with interventions such as position changes and the use of props and a rebozo to address persistent OP position in early labor; however, midwives remain uncomfortable with the techniques of digital and manual rotation. This article reviews current evidence and recommendations for the management of persistent OP position in the second stage of labor. Further research is needed to guide clinicians on the optimal timing and techniques for digital and manual rotation.